1950 Poly Royal Rodeo - Cas' Szukalski::::::photographer::: (1950)
Cal Poly student Lem Boughner competes in the calf-roping event at the 1950 Poly Royal Rodeo. This photo was reproduced in the El Rodeo Yearbook for 1950, on pg. 106. The yearbook caption reads "Lem Boughner makes his catch and prepares to tie his calf in this dramatic shot taken during the Poly Royal rodeo. The new rodeo arena proved safe and efficient and gave the audience a clear view of all eight events." An alternate version of this photo can be found here: http://digital.lib.calpoly.edu/rekl-4595 .